STRATEGICALLY ESSENTIAL ENERGY SUPPLY OBJECTS IMPORTANCE IN THE CRIMINAL LAW - Piģēns, Kārlis (Administrative and Criminal Justice, 2023)
The aim of this article is to examine strategic importance of energy supply system in the context of criminal law by performing analysis of the provisions and penalties described in the Criminal Law. Currently, Criminal Law of the Republic of Latvia has no specific sanctions against intentional or unintentional offenses to important energy supply system objects (strategically important objects), consequences of which may have a significant impact on the growth of all the Latvian economy and even have consequences to economy on regional scale.Historically, there has been a distinct understanding of significant objects of energy supply system in Latvia; hence, the Inčukalns underground gas storage is not preventively protected in a special way from the criminal law point of view, although the Criminal Code includes penalties for gas pipelines intentional destruction and damage.It would be necessary to carry out modernization and revision of the penalties provided in the Criminal Law regarding the energy sector by adjusting them according to modern safety requirements and the actual situation in the energy sector.